2017
DOI: 10.1111/mcn.12496
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and lessons learned for programme improvement of micronutrient powders interventions

Abstract: Continual course correction during implementation of nutrition programmes is critical to address factors that might limit coverage and potential for impact. Programme improvement requires rigorous scientific inquiry to identify and address implementation pathways and the factors that affect them. Under the auspices of “The Micronutrient Powders Consultation: Lessons Learned for Operational Guidance,” 3 working groups were formed to summarize experiences and lessons across countries regarding micronutrient powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 38 publications
1
49
0
2
Order By: Relevance
“…We did not assess FCHV motivation or capacity in this evaluation, but in a separate analysis from this survey population, we did find that mothers who received MNP from their FCHV were more likely to report being "very satisfied" with the performance of their FCHV (Locks et al, 2018), potentially due to improved motivation and quality of counselling. Future research and monitoring at the CHW level are essential to understand how the introduction of MNP affects CHW motivation and performance, as well as how this changes with the provision of adequate supervision and support, and also over time as programmes mature (Vossenaar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not assess FCHV motivation or capacity in this evaluation, but in a separate analysis from this survey population, we did find that mothers who received MNP from their FCHV were more likely to report being "very satisfied" with the performance of their FCHV (Locks et al, 2018), potentially due to improved motivation and quality of counselling. Future research and monitoring at the CHW level are essential to understand how the introduction of MNP affects CHW motivation and performance, as well as how this changes with the provision of adequate supervision and support, and also over time as programmes mature (Vossenaar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrient powders (MNPs)-which come in single-dose, lightweight, and shelf-stable sachets-can be mixed with a variety of semisolid foods to increase the availability of vitamins and minerals in children's diets (Zlotkin et al, 2005). Meta-analyses of randomized trials have found that regular MNP consumption can reduce the risk of anaemia and iron deficiency in children aged 6-23 months by approximately 25% and 50%, respectively (De-Regil, Suchdev, Vist, Walleser, & Peña-Rosas, 2013;Salam, MacPhail, Das, & Bhutta, 2013); however, interventions using MNP implemented outside of controlled trials have had smaller impacts (Hirve et al, 2013;Locks et al, 2017;Serdula et al, 2013;Vossenaar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the present 8 studies and the 41 studies in the systematic review, which focused largely on caregiver‐related factors affecting adherence, a year‐long consultation during the same period (Nyhus Dhillon et al, ) attempted to synthesize knowledge and experience on broader aspects of MNP programming, specifically: planning processes and supplies (Schauer et al, ), MNP delivery (models, platforms and channels), SBCC and training (Reerink et al, ) and monitoring, process evaluation and supportive supervision for continuous quality improvement (Vossenaar et al, ). This effort engaged 49 experts, from 19 countries and 25 organizations, with experience in MNP interventions, included an extensive review of published and grey literature and conducted 47 key informant interviews relative to implementation experiences in over 35 countries.…”
Section: Mnp Through the Lens Of Implementation Sciencementioning
confidence: 99%
“…Although MNP interventions have been implemented across 50 countries (United Nations International Children's Emergency Fund, ), achieving high program coverage and adherence to MNP recommendations is an ongoing challenge (Reerink et al, ). The biological pathway to impact for MNP is well articulated (De‐Regil, Suchdev, Vist, Walleser, & Peña‐Rosas, ), but program implementers are often constrained by insufficient understanding of the factors and processes underlying successful delivery of the intervention (Vossenaar et al, ).…”
Section: Introductionmentioning
confidence: 99%